Global Burden of Anxiety and Depression among Cystic Fibrosis Patient: Systematic Review and Meta-Analysis. (8th July 2021) - Guta, Mistire Teshome; Tekalign, Tiwabwork; Awoke, Nefsu; Fite, Robera Olana; Dendir, Getahun; Lenjebo, Tsegaye Lolaso
Abstract : Aims . This systemic review and meta-analysis were aimed at determining the level of anxiety and depression among cystic fibrosis patients in the world. Methods . We conducted a systematic search of published studies from PubMed, EMBASE, MEDLINE, Cochrane, Scopus, Web of Science, CINAHL, and manually on Google Scholar. This meta-analysis follows the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The quality of studies was assessed by the modified Newcastle-Ottawa Scale (NOS). Meta-analysis was carried out using a random-effects method using the STATA™ Version 14 software. Trim and fill analysis was done to correct the presence of significant publication bias. Result . From 419, 820 obtained studies, 26 studies from 2 different parts of the world including 9766. The overall global pooled prevalence of anxiety and depression after correction for publication bias by trim and fill analysis was found to be 24.91(95% CI: 20.8-28.9) for anxiety. The subgroup analyses revealed with the lowest prevalence, 23.59%, (95% CI: 8.08, 39.09)) in North America and the highest, 26.77%, (95% CI: 22.5, 31.04) seen in Europe for anxiety and with the highest prevalence, 18.67%, (95% CI: 9.82, 27.5) in North America and the lowest, 13.27%, (95% CI: -10.05, 16.5) seen in Europe for depression. Conclusion . The global prevalence of anxiety and depression among cystic fibrosis patients is common. Therefore, close monitoring of the patient, regularly screening for anxiety and depression, and appropriate prevention techniques is recommended.